DEVELOPMENT MODEL OF MILITARY TRAINING CENTER, 24TH ARMY REGION IN BECOMING A HIGH PERFORMANCE ORGANIZATION - Khaosaard, Wilailak (Journal of MCU Nakhondhat, 2024)
The objectives of this research study were to study 1) the nature of the problem and the causes of the problem and characteristics of the Military Training Center, 24th Army Region in becoming a high - performance organization 2) determines the development model the Military Training Center, 24th Army Region is becoming a high performance organization. By studying from a sample group: 1) high-ranking commanders, including the head of the preparation department head of administration and personnel head of support lecturer, head of education department and training unit commanders. 2) operational level officers include preparation officers, including administrative staff and personnel support staff education division officer and assistant teacher training unit. How to conduct research Study to the problem find the cause of the problem and determine the development model of the Military Training Center, 24th Army Region in becoming a high performance organization and analyze the characteristics of educational centers that are high performance organizations. Research tools Structured Interview (Structural Interview). Research results found that 1) The Military Training Center, 24th Army Region has been affected by the outbreak of the coronavirus 2019, thus causing educational training for military students and unable to operate as efficiently as it should including the personnel still lacking knowledge and expertise in performing their duties. Including the existing resources that are not up-to-date and insufficient to meet the needs and the budget that the unit has been allocated is limited. 2) Model for developing the Military Training Center, 24th Army Region becoming a high performance organization consisting of 7 elements, including modern organization, developing organizations to have high performance, change management, human resource development, motivation, knowledge management and leadership.